Understanding Depression Volume 1. Biomedical and Neurobiological Background (Springer Singapore, 2018)
This book, in two volumes, focuses on contemporary issues and dilemmas in relation to depression. The aim is to equip readers with an up-to-date understanding of the clinical and neurobiological underpinnings of depression and their relation to clinical manifestations and the development of more effective treatments. This first volume is devoted specifically to biomedical and neurobiological issues. Detailed information is presented on a wide range of topics, including genetics, molecular and cellular biology, and aspects at the neural circuit and multicellular system levels. Readers will gain a deeper appreciation of the factors and interactions underlying individual variation in responsiveness to stress and vulnerability to depression, as well as a clear understanding of potential treatment targets and causes of treatment resistance based on the latest research. A concluding section considers progress towards precision psychiatry and gender and cultural differences in depression. The companion volume is dedicated to clinical and management issues in depression. Understanding Depression will be an excellent source of information for both researchers and practitioners in the field.